1993
DOI: 10.1088/0960-1317/3/1/002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tip deflection and force of a bimetallic cantilever microactuator

Abstract: The authors present a model of the electromechanical performance of bimetallic cantilever microactuators by deriving the relationship between the tip deflection and change in temperature using a simple analytical approach. The model is verified by comparison with finite element analysis and published experimental data. The maximum tip force generated by a bimetallic cantilever beam is calculated by finding the reaction force needed at the tip to prevent cantilever beam deflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(136 citation statements)
references
References 6 publications
4
131
0
1
Order By: Relevance
“…The iso-voltage curves do not exhibit a linear behaviour: this was reported elsewhere for macro-scale actuators [13,14]. The maximum blocking force can be approximated, by linear extrapolation from the stiffest force versus displacement curve, at about 0.25 mN at 10 V and 0.12 mN at 5 V. Assuming a linear behaviour of the iso-voltage curves would lead to a higher value of blocking force (i.e.…”
Section: Force and Displacement Measurements Using The Calibrated Forsupporting
confidence: 53%
See 1 more Smart Citation
“…The iso-voltage curves do not exhibit a linear behaviour: this was reported elsewhere for macro-scale actuators [13,14]. The maximum blocking force can be approximated, by linear extrapolation from the stiffest force versus displacement curve, at about 0.25 mN at 10 V and 0.12 mN at 5 V. Assuming a linear behaviour of the iso-voltage curves would lead to a higher value of blocking force (i.e.…”
Section: Force and Displacement Measurements Using The Calibrated Forsupporting
confidence: 53%
“…It is common practice to estimate the blocking force knowing the moment of inertia, I and the maximum displacement (Eq. (1)) [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the heat tests, upon temperature change, the biphasic lC deflects due to the bending moment generated by the different thermal expansions of the two materials [11,20]. We have shown that PP lCs with a thin gold film on one side undergo measurable bending in response to temperature changes.…”
Section: Discussionmentioning
confidence: 88%
“…A typical MLL lens is 1 mm x 1 mm x 50 µm which yields the weight on the order of 0.15 mg. An alignment system would then have to provide adequate strength to support this weight and also have feedback mechanism that would ensure the requisite angular stability. Several MEMS driving and sensing solutions are available for these purposes, including thermal drivers, 15 electromagnetic drivers, 16 parallel plate electrostatic drivers 17 and electrostatic comb drivers. [17][18][19][20][21] One option for position feedback is piezoresistive sensing, which is easy to implement but is susceptible to ambient temperature fluctuations.…”
mentioning
confidence: 99%